"Write what I’m trying to say, not what I am saying" - Akerholt, May-Brit (Nordlit, 2015)
It is my experience that theatre artists who work with an Ibsen text agree that he understands, indeed feeds, the actor’s art; as if he ‘imagines’ how an actor will exploit the language on the page, its rhythm, sound and pace, so as to make it come alive on stage. I believe it is important as the first priority to translate the work with actors’ voices in mind. To write dialogue for a particular actor, or cast, means the language becomes idiosyncratic, characterising and thereby universal, something which is amply demonstrated by the history of playwriting. This article discusses how the making of theatre is “an encounter between actor and text in a physical environment that illuminates the world of the play” (Nick Enright). Every moment on stage is manipulated by the text. But if a translator fails to recreate the original’s world of conflicting and juxtaposed signals, the theatre artists will be unable to realise them on stage. As a translator and dramaturg I react to how the performers on the floor in front of me treat the text, as well as to the text I hold in my hand. When all the elements of text and performance come together in the rehearsal room, the plays become anchored in a specificity whose ultimate result is universality. But the article also argues that mistranslations stop this from happening. Interregnum is the process that takes place between the original play and the version in another “dress”. It involves a fine balancing act of creating a theatrical language for the target culture, while keeping the fundamental nature of the original.